Three new species of Euglossa Latreille (Hymenoptera: Apidae) from Brazil - Nemésio, André (Zootaxa, 2007)
Euglossa (Euglossella) jacquelynae sp. n., from Central Brazil, Euglossa solangeae sp. n., from coastal southeastern Brazil, and Euglossa (Euglossa) sovietica sp. n., from the western Brazilian Amazon, are described as new species. Euglossa solangeae sp. n. is believed to belong to the Euglossa stellfeldi Moure species group—a discussion on the placement of this group is also presented – and Euglossa sovietica sp. n. is treated as a member of Euglossa purpurea Friese species group.